2008
DOI: 10.1002/macp.200800345
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics of Polyurethane Formation Using a Commercial Oligomeric Diisocyanate Resin Studied by Calorimetric and Rheological Methods

Abstract: Reaction rate and kinetics of cure between PMDI and castor oil, a tri‐functional polyol, for stoichiometric and off‐stoichiometric mole ratios, were studied through isoconversional analysis of DSC data and through gelation times and viscosity build up obtained through rheological techniques. The cure kinetics of the polyurethane reaction as monitored using different techniques gave similar activation energies for the stoichiometric ratio. Isoconversional analysis of DSC data showed a competitive reaction schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…Fernandez d'Arlas et al applied DSC and Fourier transform spectroscopy for determining reaction rate of polycarbonate‐ co ‐esterdiol and diisocyanate . Papadopoulos et al reported reaction rates as well as factors for a diisocyanate polyurethane by calorimetric and rheological methods …”
Section: Introductionmentioning
confidence: 99%
“…Fernandez d'Arlas et al applied DSC and Fourier transform spectroscopy for determining reaction rate of polycarbonate‐ co ‐esterdiol and diisocyanate . Papadopoulos et al reported reaction rates as well as factors for a diisocyanate polyurethane by calorimetric and rheological methods …”
Section: Introductionmentioning
confidence: 99%
“…The two stages seen in Figure 6 arise from the difference in reactivity of the primary and secondary hydroxyl groups in the glycerol as was established using DSC. Furthermore, at each of these two stages of viscosity build up, a change in the rate is noticed, which is apparent due to the difference in reactivity of the terminal isocyanate groups to the internal isocyanate groups of the varying weight oligomers in PMDI 22. Sekkar et al48 observed a similar rate change due to the difference in reactivity of isocyanate functional groups using toluene diisocyanate.…”
Section: Resultsmentioning
confidence: 90%
“…The advanced integral isoconversional method developed by Vyazovkin20 states that at constant conversion the rate of reaction is only a function of temperature and allows the activation energy to be determined without choosing a reaction model. Isoconversional analysis has previously been used to describe the crosslinking reaction for a limited number of complex polyurethane systems 2, 21, 22. Differential scanning calorimetry (DSC) has been widely used to study thermoset reactions in both isothermal and nonisothermal modes 4, 23–27.…”
Section: Introductionmentioning
confidence: 99%
“…The first step of the dual-curing process was conducted at 60°C and the second one at 120°C. The characteristic absorbance peak of the isocyanate at 2280 cm −1 (vibration of N C O groups) was used to monitor the conversion of the isocyanate group during thiol-isocyanate reaction [23]. The disappearance of the absorbance peak at 915 cm −1 was used to monitor the reaction of epoxy groups [24].…”
Section: Characterization Techniquesmentioning
confidence: 99%